Bio-based materials for nonwovens - Santos, A. S. (2021)
The nonwoven industry is one of the most innovative and important branches of the global fiber products industry. However, the use of petrochemical-based materials in many nonwoven products leads to severe environmental issues such as generation of microplastics. Synthetic material use in nonwovens is currently around 66%. This review covers potential technologies for the use of bio-based materials in nonwoven products. The current generation of nonwoven products relies heavily on the use of synthetic binders and fibers. These materials allow for products with high functional properties, such as permanence, strength, bulk, and haptic properties. The next generation of nonwoven products will have a higher fraction of natural and renewable materials as both binders and fiber elements. There are a wide range of materials under investigation in various nonwoven product categories. Especially, lignocellulosic materials are of interest. This includes traditional pulp fibers, regenerated cellulose fibers, lignin binders and nanomaterials derived from wood. The development of water stable, strong interfiber bonding concepts is one of the main problems to be solved for advancing bio-based nonwoven products.